Technical Efficiency of Islamic Banks in ASEAN: An Examination Under Intermediation and Production Approach - Khansa Maharani, Auryn; Faturohman, Taufik (Journal of Business and Management, 2019)
This study aims to examine the relative efficiency scores of Islamic banks across six countries in ASEAN from 2011-2018 using Data Envelopment Analysis under the intermediation and production approach. The accounts used in the intermediation approach as inputs are fixed assets, staff expenses, and customer deposits, while for the production approach fixed assets andstaff expenses are used as input. The accounts used for intermediation output are loans for customers, non-interest operating income, while for the production approach the output is loans for customers, non-interest operating income, and customer deposits. The processing is divided into two frontiers, namely single-multiyear frontier to examine the efficiency trends of all ASEAN countries in eight years and cross-sectional frontier to compare the efficiency of countries in ASEAN in one year. The single multi-year frontier shows that the Philippines, Malaysia, Thailand and Singapore presents positive trend efficiency, while Indonesia fell, and Brunei fluctuated. Cross-sectional frontier shows that Brunei has the highest number of years in achieving optimum efficiency.